1171. Impact on Mortality, Length of Stay, and Antibiotic Use in Allogenic and Autologous Stem Cell Transplant Patients Colonized With Carbapenemase-Producing Enterobacteriaceae. (26th November 2018) - Ghani, Rohma; Mookerjee, Siddharth; Mullish, Benjamin; Thursz, Mark; Marchesi, Julian; Pavlu, Jiri; Davies, Frances
Abstract: Background: Carbapenemase producing Enterobacteriaceae (CPE) are increasingly impacting on patient management and hospital infection control practice. Stem cell transplant patients are among the most susceptible to invasive infections. Here we explored how this cohort are affected by CPE colonization. Methods: All patients who underwent an autologous or allograft stem cell transplant (SCT) between September 15 and December 17 at a large tertiary hospital who were CPE positive on routine rectal screening were reviewed. Length of stay (LoS) post SCT, including readmissions for sepsis and number of days of antibiotics therapy, was assessed. Controls were matched for time and type of SCT in a three controls to one case ratio. T-test was performed to analyze differences between groups (statistical significance attributed when P < 0.05). Results: The case sample had 20 SCT CPE-positive patients, of which allograft ( n = 9) and autograft ( n = 11). The control sample was made up of 59 SCT CPE-negative patients, allograft ( n = 27), and autograft ( n = 32). All patients had antibiotic therapy post SCT. Average LoS for the case sample was significantly longer in the autograft group (41.7 vs. 23.6 days, case vs. control, P = 0.01), but not significant in the allograft group (75.1 vs. 58 days, P = 0.12). Both autograft and allograft case samples had significantly longer duration of meropenem therapy, 24.8 vs. 14.4 days for allograft ( P = 0.03) and 9.4 vs. 5.5 days for autograft ( P = 0.03), cases vs. control. Colistin therapy was longer in both case samples ( P = 0.03 in autograft and P = 0.006 in allograft). Tigecycline therapy was significantly longer in the autograft case vs. control sample ( P = 0.006), with teicoplanin and piperacillin–tazobactam therapy significantly longer in the autograft case vs. control sample, P = 0.015 and P = 0.03, respectively. Conclusion: The LoS post SCT and duration of antibiotic therapy were found to be key proxy measures of worsening outcomes for CPE-positive patients vs. CPE-negative patients who had undergone SCT. Although reasons for CPE colonization vary, there appears to be an overall negative impact on patient outcomes and increased use of more toxic agents, demonstrating the need for early directed CPE decontamination therapy of these at-risk patients, such as use of Faecal Microbiota Transplant (FMT). Disclosures: All authors: No reported disclosures.